EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPETHINK TALK WRITE (TTW) BERBANTUAN MEDIA QUESTION CARD TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI BENTUK MOLEKUL BERDASARKAN TEORI HIBRIDISASI KELAS XII IPA 2 SMA PANCA BHAKTI PONTIANAK - Marhayati Marhayati; Fitriani Fitriani; Tuti Kurniati (Jurnal Ilmiah Ar-Razi, 2018)
The background of this research was the lack of student’s learning to the eleventh grade student’s of IPA 2 of SMA Panca Bhakti Pontianak in chemistry especially molecule form material based on theory hybridization. Therefore, it was needed the method of learning to increase the student’s comprehension about appropriate concept with characteristic both of the subject and student. The aim of this research was to know the differences of student’s learning result between student’s which was taught by using TTW learning method in assist of question card media with the student’s which was taught by using lecture method in molecule form material based on theory hybridization. The kind of this research wascontrol grouppretest-posttest design. The technique and the instrument to collect the data were using student’s learning test, observation, and interview. The result of data analysis showed the mean score of control class pretest was 36,91 and the mean score of posttest was 41,15 while the mean score of experiment class pretest was 31,46 and the mean score of posttest was 66,58. The statistic result of U Mann- Whitneyshowed that the score was 0,00 less than α (0,00<0,05) which meanth the differences of student’s learning result which was taught by using TTW learning method in assist of question card media with the student’s which taught by using lecture method. The increasement of student’s learning result was known by counting the effect sizescore 1,06 in high score categorize. In this case, the learning method TTW with question card can be used in molecule form material based on theory hybridization to increase the student’s learning result.Keywords: Molecule From Based on Theory Hybridization, Question Card, Think Talk Write (TTW)